An Analysis of Factors Contributing to Arabic Speaking Difficulties Among Female Students at the Indonesian Da'wah Academy (ADI) in Pabelan, Central Java - Anis Budiriyanto; Shofiyatul Muslimah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the factors contributing to the difficulties in speaking Arabic experienced by female students of the Indonesian Da'wah Academy (ADI) in Pabelan, Central Java. The research focuses on linguistic, psychological, and learning-environment factors that influence speaking skills (maharah al-kalam). This study employed a qualitative research method with a descriptive approach. Data were collected through observation, interviews, and documentation involving 11 female students of the Indonesian Da'wah Academy in Pabelan, Central Java, who served as research informants. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing.The findings reveal that the students' difficulties in speaking Arabic are caused by several factors, including limited vocabulary, insufficient mastery of grammatical structures, low self-confidence, and the lack of a supportive Arabic-speaking environment. Furthermore, the dominant use of the mother tongue in daily communication hinders the acquisition of Arabic speaking skills. Efforts to overcome these obstacles include increasing the intensity of conversation practice, creating a conducive Arabic-speaking environment, and strengthening students' motivation and confidence to speak. This study is expected to contribute to the development of more effective Arabic language learning strategies, particularly in improving students' speaking skills.